1991
DOI: 10.1007/bf01402943
|View full text |Cite
|
Sign up to set email alerts
|

Cattle feeding deterrents emitted from cattle feces

Abstract: Cattle avoid grazing forage near their feces on pasture for more than a month. The relation of cattle feces odor to the rejection was studied in feeding choice tests using cattle. The feeding deterrent of feces odor was investigated using a trough partitioned to allow passage of feces odor through test food to the cattle. The cattle did not feed from the trough containing feces 0-35 days after excretion. Volatile chemicals isolated from feces 0-35 days after excretion by a cold trap method also inhibited cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 16 publications
1
31
0
2
Order By: Relevance
“…As the solution was not applied on the forage plant itself and also offered no visual signal, it is most likely that the smell was the responsive cue for the chamois to reduce foraging. These results link to several studies that reported strong aversion towards swards treated with manure or slurry (Pain et al 1974;Suárez and Orihuela 2002) and that odour was the cue used by the animals (Dohi et al 1991;Aoyama et al 1994). Odour may convey two slightly different types of information: Firstly, odour intensity can be seen as a measure of faecal density, and secondly, strong odour in faeces could indicate reduced health and thus higher parasite load (Bekele 2002).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As the solution was not applied on the forage plant itself and also offered no visual signal, it is most likely that the smell was the responsive cue for the chamois to reduce foraging. These results link to several studies that reported strong aversion towards swards treated with manure or slurry (Pain et al 1974;Suárez and Orihuela 2002) and that odour was the cue used by the animals (Dohi et al 1991;Aoyama et al 1994). Odour may convey two slightly different types of information: Firstly, odour intensity can be seen as a measure of faecal density, and secondly, strong odour in faeces could indicate reduced health and thus higher parasite load (Bekele 2002).…”
Section: Discussionsupporting
confidence: 79%
“…Cooper et al (2000) found that sheep did not react to feeding patches experimentally infested with nematode larvae only, and although the sheep discriminated against patches contaminated with faeces, they did not discern between faeces from infected and uninfected animals. Thus, the presence of faeces rather than the parasites themselves seems to be the primary cue for risk assessment (Hutchings et al 2003), but odour may mediate the strength of the behavioural reaction (Dohi et al 1991;Aoyama et al 1994). Hutchings et al (1998) found that fresh faeces were more odoriferous and provoked stronger rejections of contaminated swards by sheep than older faeces.…”
Section: Discussionmentioning
confidence: 95%
“…O comportamento de bovinos em pastejo, relativo às suas preferências por determinadas áreas, pode ser compreendido por algumas escolhas: seleção de forragens em função de suas alturas (Black & Kenney, 1984;Arnold, 1987;Bazely, 1990), ou das variações nos teores de nutrientes (Bazely, 1990;Langvatn & Hanley, 1993;Wallisdevries & Schippers, 1994), ou ainda a seleção de áreas não contaminadas com placas de fezes (Dohi et al, 1991;Hutchings et al, 1998;Pascoa, 2005). Outros autores indicaram que os principais mecanismos de escolha são relacionados com a disponibilidade e distribuição de certos recursos, principalmente a água, mas também os minerais, tanto os encontrados nas plantas quanto em suplementos (Adler et al, 2001;Ganskopp, 2001).…”
Section: Situação Atual Da Aplicação Do Sig Em Estudos Com Bovinosunclassified
“…Mammalian herbivores may use sward height and sward tone as cues to determine the potential forage intake rate and N content of swards, respectively (Black and Kenney 1984;Arnold 1987;Bazely and Ensor 1989;Bazely 1990), and olfactory cues to determine faecal and thus parasite-contaminated swards (Dohi et al 1991;Hutchings et al 1998). These environmental cues may enable grazing mammals to assess the relative costs and benefits of a grazing trade-off, which in turn determines their grazing strategy (Lafferty 1992).…”
Section: Introductionmentioning
confidence: 99%